The effect of pentagamavunon-0 pretreatment to the pharmacokinetic of paracetamol profile on wistar male rats - Wahyono, Djoko; Hakim, Arief Rahman (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Drug interaction can happen when two or more drugs are given together. This research was aimed to observe the effect of PGV-0 pretreatment to paracetamol pharmacokinetic profile in male rats.The study was conducted employing a one-way randomized completely design, using male Wistar rats weight 150 g (±10%). The animals were divided into three groups (5 rats for each group). Group I (control) was given a single oral paracetamol 150 mg/kg BW. The other groups II dan III were given a single oral PGV-0 20 and 40 mg/kg BW one hour before treatment with paracetamol respectively. After all rats were pretreated, serial blood and urine samples were withdrawn and were analysed using HPLC for unchanged paracetamol. Pharmacokinetic parameters of paracetamol i.e. Cmax, tmax, AUC, K, t1/2, Vdss/F, Cl/F, Aecum, dan %fe were determined based on concentration to time data in the blood and urine. The paracetamol pharmacokinetic parameters were analyzed by one-way analysis of varians (ANOVA) using 95% confidence interval. And the difference between groups were analyzed using Tukey-test method. The results showed that the pharmacokinetic parameters of paracetamol in the animals prefed with PGV-0 20 and 40 mg/kg BW did not change significantly (P > 0.05).Key words : pharmacokinetics, interaction, paracetamol, Pentagamavunon-0